2005
DOI: 10.1590/s1413-86702005000300004
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility of Gram-negative bacteria in Brazilian hospitals: the MYSTIC Program Brazil 2003

Abstract: Establish the susceptibility pattern of Gram-negative bacteria causing infections in ICU patients, MYSTIC Program Brazil 2003. Gram-negative bacteria (n = 1,550) causing nosocomial infections were collected at 20 Brazilian centers. The central laboratory confirmed the identification and performed the susceptibility tests by Etest methodology (AB Biodisk, Solna, Sweden) for meropenem, imipenem, ciprofloxacin, ceftazidime, cefepime, cefotaxime, piperacillin/tazobactam, gentamicin, and tobramycin. Interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
22

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 22 publications
3
30
0
22
Order By: Relevance
“…6 Data from the MYSTIC study from South America showed 52% of resistance to cefepime, which can be a surrogate for ESBL strains. 7 Use of beta-lactam antibiotics containing an oxyimino group (cefuroxime, ceftriaxone, cefotaxime, ceftazidime, or aztreonam) are risk factors for ESBL-KP. [8][9][10][11] Nevertheless, time to use this group of drugs should not be guided by hospitalization length, because we could not correlate increased resistance with duration of hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…6 Data from the MYSTIC study from South America showed 52% of resistance to cefepime, which can be a surrogate for ESBL strains. 7 Use of beta-lactam antibiotics containing an oxyimino group (cefuroxime, ceftriaxone, cefotaxime, ceftazidime, or aztreonam) are risk factors for ESBL-KP. [8][9][10][11] Nevertheless, time to use this group of drugs should not be guided by hospitalization length, because we could not correlate increased resistance with duration of hospitalization.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the frequency of ESBL-producing K. pneumoniae in Brazilian hospitals has been higher than that observed in many European and US hospitals, accounting for approximately 50 % of K. pneumoniae strains recovered from intensive care units (Kiffer et al, 2005;Paterson & Bonomo, 2005) and related to high mortality rates (Marra et al, 2006). This widespread occurrence of ESBLs should provide a salutary lesson from which we should draw experience to aid us in combating the spread of MBLs (Paterson & Bonomo, 2005;Walsh et al, 2005).…”
mentioning
confidence: 99%
“…A resistência bacteriana é uma preocupação mundial, sendo objeto de estudo das mais diversas pesquisas (Sader et al, 2001;Kiffer et al, 2005;Theuretzbacher, 2012).…”
Section: Discussionunclassified
“…Concomitantemente ao seu uso, surgiram os isolados apresentando resistência, como pode ser observado na Figura 2 (Davies, Davies, 2010 (Gales et al, 2012;Girão et al, 2008;Kiffer et al, 2005;Lincopan et al, 2005;2006;Pavez et al, 2009;Rossi, 2011;Sader et al, 2001;Theuretzbacher, 2012). O tratamento de pacientes com infecções hospitalares graves utilizando antibióticos de amplo espectro de atividade, como os carbapenêmicos, deve-se a sua boa permeabilidade através da membrana externa bacteriana e estabilidade frente a muitas β-lactamases (Franco et al, 2010;Fritsche et al, 2005;Gales et al, 2003).…”
Section: O Uso Excessivo De Antibióticos E a Infecção Hospitalarunclassified